Analysis of shrinkage on thick plate part using genetic algorithm - Siti Noor Najihah Mohd Nasir (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Injection moulding process has been widely used to produce plastic products with various shapes for high productivity and high volume products with low cost. However there are several defect which can influence the quality of the moulded part. The most common defect is shrinkage. shrinkage problem perfectly but it can be reduced.To overcome this problem, Genetic algorithm (GA) is used. Most of researchers use GA method to find the shrinkge especially for thin part but hardly to found researches that use GA methond for optimising a thick plate part.